2009
DOI: 10.1002/ccd.21849
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death complicating alcohol septal ablation: A case report and review of literature

Abstract: Over the years, alcohol septal ablation has become an effective and well-accepted modality in the treatment of patients with hypertrophic obstructive cardiomyopathy refractory to standard medical therapy. Malignant tachyarrythmias infrequently complicates the procedure and are usually self-terminating. We describe a case of alcohol septal ablation complicated by sudden cardiac death occurring immediately following the procedure requiring prolonged resuscitative efforts with eventual complete recovery. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Sustained ventricular tachycardia has been rarely reported following the ASA and only few reports described it as an early post‐procedural complication [8, 14–17]. However surprisingly, Alam et al reported in a systematic review of the literature occurrence of postprocedural ventricular fibrillation 2.2%[2].…”
Section: Discussionmentioning
confidence: 99%
“…Sustained ventricular tachycardia has been rarely reported following the ASA and only few reports described it as an early post‐procedural complication [8, 14–17]. However surprisingly, Alam et al reported in a systematic review of the literature occurrence of postprocedural ventricular fibrillation 2.2%[2].…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular arrhythmias have been reported in the early postprocedural phase, possibly as an effect of ischemia. 67,83- 85 With the exception of 1 study, 86 long-term follow-up data have described ventricular arrhythmias as a rare event. 32- 35 In contrast, no increased risk of malignant arrhythmias after the procedure has been shown in patients who already had an ICD implanted because of a previously estimated high risk of sudden death.…”
Section: Complicationsmentioning
confidence: 99%